Effect of flocculant dosage on the settling properties and underflow concentration of thickener for flocculated tailing suspensions - Lianfu Zhang; Hongjiang Wang; Aixiang Wu; Ke Yang; Xi Zhang; Jiabin Guo (Water Science and Technology, 2023)
Flocculation is important in the thickening process to improve the underflow concentration in thickeners for tailing suspensions. Traditional zone settling velocity (ZSV) functions ignore the effect of flocculant dosage on the ZSV and the thickening behavior of thickeners. To investigate the effect of flocculant dosage on the settling flux function, a series of batch settling tests were conducted at various flocculant dosages for unclassified and fine tailings. The correlation among flocculant dosage, solid fraction, and parameters in the ZSV function was revealed. Moreover, a simulation of continuous thickening based on the ZSV function was performed. Results indicated that flocculation influenced settling velocity and floc density. With an increased flocculant dosage, the settling velocity of floc increased, resulting in increased underflow concentration. Conversely, floc density decreased due to a stronger particle–particle interaction, leading to a decreased underflow concentration. HIGHLIGHTS Zhang's approach is validated for tailings at various initial solid fractions.; The correlation among flocculant dosage, solid fraction, and parameters in the ZSV function was revealed.; The coupling effect mechanism of flocculant dosage and solid fraction on thickening is proposed.;